2012
DOI: 10.1371/journal.pone.0047140
|View full text |Cite
|
Sign up to set email alerts
|

Second-to-Fourth Digit Ratio and Impulsivity: A Comparison between Offenders and Nonoffenders

Abstract: Personality characteristics, particularly impulsive tendencies, have long been conceived as the primary culprit in delinquent behavior. One crucial question to emerge from this line of work is whether impulsivity has a biological basis. To test this possibility, 44 male offenders and 46 nonoffenders completed the Eysenck Impulsivity Questionnaire, and had their 2D∶4D ratio measured. Offenders exhibited smaller right hand digit ratio measurements compared to non-offenders, but higher impulsivity scores. Both im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Other authors have already found a relationship between low educational level and juvenile delinquency. 18,27 Nevertheless, when ANCOVA was carried out taking into account the differences in years of schooling between the two groups, the difference in mean PCL-R scores remained statistically significant (p , 0.01). Hence, we can conclude that psychopathic traits assessed by PCL-R were independent from educational level at the f 0.05 significance level.…”
Section: Discussionmentioning
confidence: 95%
“…Other authors have already found a relationship between low educational level and juvenile delinquency. 18,27 Nevertheless, when ANCOVA was carried out taking into account the differences in years of schooling between the two groups, the difference in mean PCL-R scores remained statistically significant (p , 0.01). Hence, we can conclude that psychopathic traits assessed by PCL-R were independent from educational level at the f 0.05 significance level.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have established a link between personality and risk taking (Breivik, ; Levenson, ; Nicholson, Soane, Fenton‐O'Creevy, & Willman, ; Zuckerman & Kuhlman, ). Moreover, male prisoners and nonprisoners seem to differ in personality characteristics, with prisoners being more impulsive than nonprisoners (Hanoch et al, ; Rolison, Hanoch, & Gummerum, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that prisoners are more likely to engage in substance abuse, unsafe sex, and gambling than are nonprisoners (Fazel, Bains, & Doll, ; Frost & Tchertkov, ; Hanoch & Gummerum, ; Lahn, ). They also have higher levels of sensation seeking (Wilson & Daly, ) and impulsivity (Hanoch, Gummerum, & Rolison, ), characteristics that are related to risk taking. In addition, prisoners score higher on instruments specifically developed to measure the tendency to take risks.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…208-213;Klinesmith, Kasser, & McAndrew, 2006). Furthermore, studies based on the 2D:4D biomarker have implicated prenatal brain exposure to high testosterone as a predictor of aggression (Bailey & Hurd, 2005;Hönekopp & Watson, 2011;Trivers, Manning, & Jacobson, 2006) as well as various forms of criminality Hanoch, Gummerum, & Rolison, 2012;.…”
Section: Perinatal and Postpubertal Effects Of Androgensmentioning
confidence: 99%